Optimizing the use of Data Management via Market Intelligence to optimize spending in Indonesian Oil and Gas Sectors - Sjah Razad, Haryo Seto (Swiss German University, 2015)
Any purchasing or product and service acquisition comes in hidden costs if we dont have background information on references of reference database. Especially in the oil and gas sector where the cost to acquire those services are higher, market intelligence initiatives plays a pivotal role in ensuring we obtain correct market price data with the help of COBIT5 framework